1982
DOI: 10.1126/science.215.4539.1498
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Land-Surface Evapotranspiration on the Earth's Climate

Abstract: Calculations with a numerical model of the atmosphere show that the global fields of rainfall, temperature, and motion strongly depend on the land- surface evapotranspiration. This confirms the long-held idea that the surface vegetation, which produces the evapotransporation, is an important factor in the earth's climate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
563
0
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,049 publications
(580 citation statements)
references
References 3 publications
12
563
0
5
Order By: Relevance
“…Both root zone soil moisture and vegetation conditions play a vital role in the partitioning of water and energy budgets at the soilvegetation-atmosphere interface through evaporation processes of the uppermost surface soil layer and plant transpiration [Shukla and Mintz, 1982]. This partitioning, in turn, partly controls the thermodynamic and soil moisture content of the lower troposphere, and thus, climate.…”
Section: Introductionmentioning
confidence: 99%
“…Both root zone soil moisture and vegetation conditions play a vital role in the partitioning of water and energy budgets at the soilvegetation-atmosphere interface through evaporation processes of the uppermost surface soil layer and plant transpiration [Shukla and Mintz, 1982]. This partitioning, in turn, partly controls the thermodynamic and soil moisture content of the lower troposphere, and thus, climate.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of soil water in Earth's climate system has been demonstrated using general circulation models (GCMs) and documented by numerous authors [e.g., Manabe, 1969; Shukla and Mintz, 1982;Milly and Dunne, 1994;Dirmeyer, 1995] (see also Entekhabi et al [1996] for a recent review). For example, soil water links the water, energy, and biogeochemical cycles; its high heat capacity provides thermal inertia over multiple timescales; and it fuels evapotranspiration, which helps to sustain storms through the process of precipitation recycling [Brubaker et al, 1993;Eltahir and Bras, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed by , several numerical experiments with atmospheric general circulation models have been carried out to investigate the sensitivity of the climate to the land-surface boundary conditions including soil moisture [Walker and Rowntree, 1977;Shukla and Mintz, 1982;Rind, 1982;Rowntree and Bolton, 1983;Yeh et al, 1984]. These studies demonstrated the general tendency that a wetter land surface, and therefore a larger evaporation, is accompanied by a larger precipitation over the land.…”
Section: Introductionmentioning
confidence: 99%